2018
DOI: 10.1007/s11356-018-2271-0
|View full text |Cite
|
Sign up to set email alerts
|

Insight into elemental mercury (Hg0) removal from flue gas using UV/H2O2 advanced oxidation processes

Abstract: Elemental mercury (Hg) emitted from coal-fired power plants and municipal solid waste (MSW) incinerators has caused great harm to the environment and human beings. The strong oxidized OH radicals produced by UV/HO advanced oxidation processes were studied to investigate the performance of Hg removal from simulated flue gases. The results showed that when HO concentration was 1.0 mol/L and the solution pH value was 4.1, the UV/HO system had the highest Hg removal efficiency. The optimal reaction temperature was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…All the computational calculations were performed using the Gaussian 09 program package (Gaussian, Inc., Wallingford CT, USA). 32 Based on the experimental analysis, quantum chemistry calculations were carried out using density functional theory (DFT) and the Becke three-parameter Lee− Yang−Parr (B3LYP) method. The 6-31+G(d,p) basis set was used for geometrical optimization and vibrational frequencies of reactants (R), transition states (TS), and products (P).…”
Section: Contribution Analysis Of Differentmentioning
confidence: 99%
“…All the computational calculations were performed using the Gaussian 09 program package (Gaussian, Inc., Wallingford CT, USA). 32 Based on the experimental analysis, quantum chemistry calculations were carried out using density functional theory (DFT) and the Becke three-parameter Lee− Yang−Parr (B3LYP) method. The 6-31+G(d,p) basis set was used for geometrical optimization and vibrational frequencies of reactants (R), transition states (TS), and products (P).…”
Section: Contribution Analysis Of Differentmentioning
confidence: 99%
“…Rapid economic development is accompanied by the accelerated consumption of industrial energy, and the position of coal as an important primary energy source in the industrial development cannot be ignored. , However, the burning of coal is inevitably accompanied by serious environmental pollution. Take the heavy metal mercury as an example, its presence brings irreversible damage to the energy environment and human health. , Mercury in coal combustion flue gas is usually present in three forms: elemental mercury (Hg 0 ), oxidized mercury (Hg 2+ ), and particulate bound mercury (Hg p ). Hg 2+ and Hg p are soluble and easily adsorbed by particulate matter, which can be effectively captured by wet flue gas desulfurization (WFGD) systems and dust removal equipment (e.g., electrostatic precipitators, baghouses). Nevertheless, Hg 0 is difficult to remove due to its special chemical properties (insoluble in water, high volatility, etc.) and is usually converted to the oxidized mercury for removal. Therefore, the key technology for the removal of elemental mercury lies in its efficient conversion to Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, •OH was the key core of this technology. Based on current studies, several methods have been used to catalyze the decomposition of H 2 O 2 , mainly for heterogeneous Fenton reaction and ultraviolet treatment. , Compared with ultraviolet treatment, the heterogeneous Fenton reaction was an economic and feasible approach for catalyzing the decomposition of H 2 O 2 . , Ding et al utilized hematite to catalyze the decomposition of H 2 O 2 and integrated it with an ammonia-based washing tower for simultaneous removal of NO x and SO 2 , which achieved respectable removal efficiency (80% for NO x and 98% for SO 2 ) . Moreover, it was reported that the generation of oxygen vacancies benefited the catalytic decomposition of H 2 O 2 by their further research, which could enhance NO x removal efficiency .…”
Section: Introductionmentioning
confidence: 99%